Multiple-cation wide-bandgap perovskite solar cells grown using cesium formate as the Cs precursor with high efficiency under sunlight and indoor illumination. Issue 29 (19th July 2022) - Guo, Qiang; Ding, Yuanjia; Dai, Zheng; Chen, Zongwei; Du, Mengzhen; Wang, Zongtao; Gao, Lei; Duan, Chen; Guo, Qing; Zhou, Erjun
Abstract : Using cesium formate as the Cs precursor, wide-bandgap perovskite solar cells achieve high efficiencies of 20.01% under AM1.5G illumination and 38.52% under LED light illumination (2700 K, 1000 lux). Abstract : Owing to the advantages of adjustable bandgap, low-cost fabrication and superior photovoltaic performance, wide-bandgap (WBG) perovskite solar cells (PSCs) are considered as the promising top-cell for multi-junction solar cells. At the same time, WBG PSCs have also shown great potential for indoor photovoltaic applications. To further improve the performance of WBG PSCs, in this work, we fabricated efficient WBG PSCs via introducing cesium formate (CsFa) as the Cs precursor. Due to the HCOO·Pb + and HCOOH·Cs + complex formation and HCOOH volatilization accompanying the crystallization process, the crystallization of the perovskite using the CsFa precursor (CsFa-perovskite) is promoted. Compared to the perovskite prepared using the CsBr precursor (CsBr-perovskite), the WBG CsFa-perovskite shows better perovskite crystallization, reduced trap-state density, and better phase stability under light illumination. Finally, the 1.63 eV WBG PSCs based on the CsFa-perovskite achieve a significant PCE of 20.01% under one sun illumination (AM 1.5G, 100 mW cm −2 ), which is higher than that of PSCs based on the CsBr-perovskite (18.27%). Moreover, the PCE of CsFa-perovskite PSCs also under indoor warm-white 2700 K LED light illumination (1000 lux) is as high as 38.52%. Our results demonstrate that CsFa as the Cs precursor is a promising candidate to promote the device performance of WBG PSCs.